Pengaruh Disiplin Belajar, Fasilitas Belajar Terhadap Prestasi Belajar Melalui Proses Pembelajaran UPPBJ Makassar Universitas Terbuka Pokjar Kabupaten Luwu Utara - Ahmad Sigit; Muh. Alwi; Burhan Burhan; Muh. Ali (Jurnal Sinestesia, 2022)
This study aims to (i) determine whether there is an effect of learning facilities on the student learning achievement of Pokjar Luwu Utara; (ii) determine whether there is an effect of learning discipline on student achievement of Pokjar Luwu Utara; (iii) determine whether there is an effect of learning facilities on student achievement of Pokjar Luwu Utara through the learning process; (iv) determine whether there is an effect of learning discipline on student achievement of Pokjar Luwu Utara through the learning process; and (v) determine whether there is an effect of tutor discipline and learning facilities on learning achievement through the learning process of the Luwu Utara Pokjar students. The research method uses a quantitative approach, and the type is correlational research with an ex-post facto design. The data collection technique is primary data that comes directly from the research subject. The population is 230 students at UPPJB-UT Makassar Pokjar Luwu Utara. The sampling technique used was random sampling so that 103 people were obtained. The data analysis technique used is descriptive analysis, path analysis requirements test, and hypothesis testing. The results showed that the learning facilities had an effect on the learning achievement of Pokjar Luwu Utara students; learning discipline has an effect on the learning achievement of Pokjar Luwu Utara students; learning facilities have an effect on the learning achievement of Pokjar Luwu Utara students through the learning process; learning discipline has an effect on the learning achievement of Pokjar Luwu Utara students through the learning process; learning facilities have an effect on learning achievement through the learning process of the Pokjar Luwu Utara students.